2020
DOI: 10.48550/arxiv.2010.00779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Planning a Sequence of Base Positions for a Mobile Manipulator to Perform Multiple Pick-and-Place Tasks

Abstract: In this paper, we present a planner that plans a sequence of base positions for a mobile manipulator to efficiently and robustly collect objects stored in distinct trays. We achieve high efficiency by exploring the common areas where a mobile manipulator can grasp objects stored in multiple trays simultaneously and move the mobile manipulator to the common areas to reduce the time needed for moving the mobile base. We ensure robustness by optimizing the base position with the best clearance to positioning unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Gonc xalves et al 9 compared the efficiency and effectiveness of four state-of-the-art evolutionary algorithms considering the collision avoidance for the mobile manipulator, and found that Parato-based algorithms are suitable for off-line trajectory planning. Xu et al 10 presented a base positions planning method to search for the shortest path for a mobile manipulator, including steps of IK solutions, reachability database construction, base positioning uncertainty analysis and path planning. Pajak and Pajak 11 described a holonomic mobile humanoid manipulator and proposed its motion planning under an industrial environment, which considers mechanical limitations, collisions avoidance and manipulation dexterity.…”
Section: Introductionmentioning
confidence: 99%
“…Gonc xalves et al 9 compared the efficiency and effectiveness of four state-of-the-art evolutionary algorithms considering the collision avoidance for the mobile manipulator, and found that Parato-based algorithms are suitable for off-line trajectory planning. Xu et al 10 presented a base positions planning method to search for the shortest path for a mobile manipulator, including steps of IK solutions, reachability database construction, base positioning uncertainty analysis and path planning. Pajak and Pajak 11 described a holonomic mobile humanoid manipulator and proposed its motion planning under an industrial environment, which considers mechanical limitations, collisions avoidance and manipulation dexterity.…”
Section: Introductionmentioning
confidence: 99%